Vertical Electrolyte‐Gated Transistors: Structures, Materials, Integrations, and Applications - Bin Bao; Ting Zhang; Junlei Xie; Jin Wu; Gang He; Lang Jiang; Yanlin Song; Shouguo Wang (Advanced Electronic Materials, 2025)
Abstract Biological synapse‐inspired electrolyte‐gated transistors have received broad attention recently as a competitive candidate for constructing artificial intelligence (AI) systems to meet the data memorizing and processing challenges brought by the big data era. Vertically structured electrolyte‐gated transistors, which decouple the channel length of the transistors from the resolution of photolithography and printing techniques, enjoy significantly improved electrical performances compared to their planar counterparts. The vertical electrolyte‐gated transistors (vEGTs) are constructed in different device architectures by diverse materials, and integrated into circuits with hierarchical level of sophistication. Benefiting from their unique device structures, a wealth of available component materials and integration strategies, vEGTs are finding their pathway toward diverse applications such as synaptic emulating, neuromorphic computing, and biological sensing. Herein, recent progress on the vEGTs is reviewed. Three typical device structures for the vEGTs are categorized and exemplified. The materials used to construct the semiconductor channels and the ion‐conducting electrolytes are presented. The electrical performances of typical vEGTs are briefly discussed. The integration strategies and application fields of the vEGTs are summarized. At the end, the challenges for the further development of advanced vEGTs are discussed.